Sentencing in Lithuania: Practice and Meaning - Sakalauskas, Gintautas (Sociologija. Mintis ir veiksmas, 2007)
The aim of the article is to analyse the practice of sentencing in Lithuania, its changes and tendencies. The incanceration rates in Lithuania are one of the highest among the European Countries despite the minor difference in reported crime rates. The questions the dominant "corrective" conception and suggest that clearly defined purpose of re-socialization could the grounds to reform the system of imprisonment.